Participative budgeting: the effects of budget emphasis, information asymmetry and procedural justice on slack - additional evidence / Vincent K Chong and Raymon Strauss - K Chong, Vincent; Strauss, Raymon (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2017)
This study re-examines the results presented in Lau and Eggleton (Accounting and Business Research, 2003, pp. 91-104) regarding the influence of information asymmetry and budget emphasis on the relationship between budgetary participation and budgetary slack hold based on a different sample. In addition, this study extends Lau and Eggleton’s research model by incorporating procedural justice as an additional moderating variable. A survey research methodology was used to collect data. Participants consisted of 116 managers from Australian manufacturing firms listed in the Who's Who in Business in Australia database. The results indicate that subordinates’ propensity to create budgetary slack is low when budgetary participation, information asymmetry and budget emphasis are all high. In addition, the results reveal that in high budget emphasis and high information asymmetry situations, subordinates’ propensity to create budgetary slack is low when budgetary participation and procedural justice are high. This study contributes to the existing knowledge by generating both theoretical and practical implications to improve budgetary control systems within organizations.